(-3).(-4).(-5).(-6)=
=(+12).(-5).(-6)=
=(60).(-6)=
Soluções para a tarefa
Respondido por
0
Resposta:
(-3).(-4).(-5).(-6)=
(+12).(-5).(-6)=
(60).(-6)=
Respondido por
0
Resposta:
(-3)•(-4)•(-5)•(-6)= 360
12 × -5 = -60
-60 × -6 = 360
60 × (-6) = 360 ou seja SEGUE uma regra de ( - ) + ( - ) = +
( + ) + ( - ) = -
então a resposta é -360
Explicação passo-a-passo:
espero ter ajudado ✌
Perguntas interessantes
Inglês,
7 meses atrás
Português,
7 meses atrás
Pedagogia,
8 meses atrás
Geografia,
8 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás